2016
DOI: 10.20950/1678-2305.2016v42n3p578
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements and parasitism in Nile tilapia farmed in the Southern Brazil

Abstract: This study evaluated the trace elements and parasitological indices in Nile tilapia examined from two different facilities, named as swine-consorted, using pig manure, and monoculture. For trace element analysis, the fish muscle tissue was collected individually in each facility. Each portion was weighed, dried in a stove at 60°C for 48 h and analyzed by Energy Dispersive X-ray Fluorescence Spectrometry (EDXRF). Parasitological analysis followed the routine method for parasites collection, quantification and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…All parasites identified in the present study were previously identified parasitizing tilapia (Ghiraldelli et al 2006a, b;Martins and Ghiraldelli 2008;Jero ˆnimo et al 2010, b;Valladao et al 2014;Nunes et al 2016). However, the species were all identified in farmed tilapia, different from those verified in the present study as well, no zoonotic parasites were identified.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…All parasites identified in the present study were previously identified parasitizing tilapia (Ghiraldelli et al 2006a, b;Martins and Ghiraldelli 2008;Jero ˆnimo et al 2010, b;Valladao et al 2014;Nunes et al 2016). However, the species were all identified in farmed tilapia, different from those verified in the present study as well, no zoonotic parasites were identified.…”
Section: Discussionsupporting
confidence: 67%
“…The basin of the Cachoeira river is located in Joinville, the most populous city in the state of Santa Catarina, Brazil (Ribeiro and Oliveira 2014), and receives contaminating effluents, mainly from the Industrial District where there are metal, textile and plastic industries, as well as The city holds a few fish farms (Ghiraldelli et al 2006a, b;Jero ˆnimo et al 2011b;Nunes et al 2016;Steckert et al 2018) therefore, unintentional fish getaways might occur. Thus, it might be happening at the Cachoeira river with tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…(Azevedo et al, 2006;Ghiraldelli et al, 2006a;Jerônimo et al, 2011;Zago et al, 2014;Nunes et al, 2016) and the protozoans have been shown to be the most prevalent group in Santa Catarina. Ranzani-Paiva et al (2005), in a study with Nile tilapia from a reservoir in São Paulo, observed among other parasites, Trichodina (Azevedo et al, 2006;Ghiraldelli et al, 2006a;Jerônimo et al, 2011;Nunes et al, 2016). The above suggests a possible variation of the parasitological fauna of Oreochromis niloticus among the fish farms and along with culture cycles in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that parasites are also vectors of other pathogens, which can lead to acute mortality of fish (Xu et al, 2012;Pilloux et al, 2015). Ectoparasites are common in tilapia culture and have been reported by several authors (Ghiraldelli et al, 2006a;Jerônimo et al, 2011;Tavares-Dias et al, 2013;Nunes et al, 2016) and according to Moraes & Martins (2004) are directly related to water quality and animal management.…”
Section: Introductionmentioning
confidence: 96%
“…Considering the socioeconomic importance of Nile tilapia (Oreochromis niloticus) within Brazilian aquaculture and the economic impact of parasitic diseases, very little information on these groups is available. Only three out of the eleven genera of the family Trichodinidae have so far been reported parasitizing Nile tilapias in Brazil, namely Trichodina Ehrenberg, 1838 (Trichodina centrostrigeata Basson, Van As and Paperna, 1983, T. compacta Van As and Basson, 1989, T. heterodentata Duncan, 1977 Van As and Basson, 1989, T. migala Van As and, Paratrichodina Lom, 1963 (Paratrichodina africana Kazubski andEl-Tantawy, 1986) and Tripartiella Lom, 1959(Tripartiella orthodens Basson and Van As, 1987) (GHIRALDELLI et al, 2006MARTINS & GHIRALDELLI, 2008;PANTOJA et al, 2012;VALLADÃO et al, 2013VALLADÃO et al, , 2016ZAGO et al, 2014;NUNES et al, 2016).…”
Section: Introductionmentioning
confidence: 99%